PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 105 PEKANBARU - Elsa Astari Astari; Gustimal Witri Witri; Lismasila ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research carried out base on the lowly of the result of mathematics in grade 4th SDN 105 Pekanbaru which is about 63,09 within minimal completeness criterion stated is 70. Among 33 student, there was only 10 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on mathematics of the 4th graders in SDN 105 Pekanbaru with the application of contextual teaching and learning model. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of contextual teaching and learning model it was abtained student’s outcomes in UH I within average 73,50 (improved from basic score 16,50%). The average score form UH II was 86,72 (improved 37,45%). Teachers activities results in the cycle I was 87,5% (very good category). Meanwhile in the second cycle was 92,18% (very good category). Students activity in the cycle I was 70,31% (good category). And then, in the cycle II was 87,5% (very good category. Based on the result it can be concluded that implementation of contextual teaching and learning model can mathematics in 4th graders at SDN 105 Pekanbaru Keywords : Contextual Teaching and Learning, Students Achievement the Result Of Mathematics Studies.